Aspek Klinik dan Karakteristik Tipe Histopatologik Timoma - Maria Mayella Vianney; Lisnawati Rachmadi (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2021)
BackgroundThymoma is the most common neoplasm found in thymus gland and is classified into 5 main histopathological types, A, AB, B1, B2,and B3. Thymomas are most commonly found in the anterior mediastinum and accompanied with myasthenia gravis. The aim of thisstudy was to find out clinical feature and histopathological characteristics of thymomas in Department of Anatomical Pathology, Facultyof Medicine, University of Indonesia/Dr. Cipto Mangunkusumo Hospital (FKUI/RSCM) in 2014-2018.MethodsThis is a descriptive study, using a cross-sectional design. Clinical and histopathological data obtain from the medical records andarchives of the Department of Anatomical Pathology of FKUI/RSCM. Clinical data consists of age, sex, tumor location, clinicalsymptom, concomitant disease, metastasis, and treatment. Histopathological assessment consists of histopathology type using WorldHealth Organization criteria and staging using Masaoka-Koga staging system.ResultsThere were 31 thymoma cases matched the inclusion criteria. Nineteen (61.3%) of 31 cases were women. The mean age of thesubjects was 46.7 years old. A total of 12 cases (37.5%) had muscle weakness due to myasthenia gravis as chief complaint and 21cases (67.7%) of tumor mass in the anterior mediastinum. There 9 cases of type AB and 2 cases of type B2.ConclusionThymoma is more common in women with an average age of 46.7 years. The most common paraneoplastic syndrome is myastheniagravis and mostly found in the anterior mediastinum. The most common histopathologic type is type AB, while type B2 is the least.